Pengaruh Free Cash Flow, Leverage, Likuiditas, Profitabilitas, Dan Ukuran Perusahaan Terhadap Manajemen Laba(Studi Empiris pada Perusahaan Manufaktur yang Terdaftardi Bursa Efek Indonesia Periode 2012-2015) - WININGSIH, WININGSIH, Dr.Triyono, S.E., M.Si (2017)
The aims of the research to examine the effect of free cash flow, leverage, liquidity, profitability, and firm size on earnings management. Population of this research is all of listed manufacturing firms in Indonesia Stock Exchange starting from 2012 until 2015. The sampling method use purposive sampling method with the total sample as much as 82 companies. Technique of analysis data used the classic assumptions test, they are normality test, multicollinearity test, heteroscedasticity test, and autocorelation test. Hypothesis test used multiple regression analysis. The results show that profitability have effect on earnings management. While free cash flow, leverage, liquidity and firm size have no effect on earnings management